Water management can alleviate the deterioration of rice quality caused by high canopy humidity - Le Chen; Xueyun Deng; Hongxia Duan; Xueming Tan; Xiaobing Xie; Xiaohua Pan; Lin Guo; Hui Gao; Haiyan Wei; Hongcheng Zhang; Tao Luo; Xinbiao Chen; et al. (Agricultural Water Management, 2023)
This study conducted a two-year field artificial intelligence (AI) greenhouse rice planting experiment with different canopy humidity (normal humidity, NH; high humidity, and HH) and irrigation regimes (continuous flooding, CF; drought cultivation, DC; alternate wetting-drying, AWD) to test whether high canopy humidity from heading to maturity deteriorates rice grain quality, whether appropriate water management can alleviate these adverse effects, and the related mechanisms. The results showed that compared with NH, HH significantly decreased the head rice rate while increasing the protein, amino acid, amylopectin, amylose, and chalkiness. Moreover, HH significantly decreased the peak viscosity, breakdown, and number of small starch granules, while increasing the setback, number of large starch granules, relative crystallinity, gelatinization temperature, and enthalpy. Under NH and HH, AWD treatment resulted in a higher head rice rate, peak viscosity, breakdown, key enzyme activities of starch synthesis, amylose, amylopecan, relative crystallinity, small starch granules, gelatinization temperature, and enthalpy than DC and CF treatments, while lower chalkiness, setback, protein, amino acid, and large starch granules were observed. HH increased the chalkiness by promoting the formation of large starch granules, thus reducing the milling quality. The increase in amylose and relative crystallinity further causes HH to deteriorate the cooking and eating quality. AWD could alleviate the deterioration of rice grain milling, appearance, and eating quality caused by HH by improving starch granules.